TAMI-43. HYPOXIC REGULATION OF GLIOBLASTOMA TUMOR GROWTH THROUGH L(3)MBTL1. (12th November 2021) - Shih, Ling-Kai; Mukherjee, Subhas; Brat, Daniel
Abstract: Glioblastoma (GBM) is the deadliest and most common of all primary brain tumors. Drosophila brain tumor models have uncovered signaling pathways regulating tumor growth that are highly conserved in GBM. Our search for a novel tumor suppressor using Drosophila led to Lethal (3) malignant brain tumor [l(3)mbt], temperature-sensitive mutants of which cause neuroepithelial tumor-like overproliferation in optic lobes. dL(3)MBT and its human orthologs L3MBTL1-L3MBTL4 all harbor Malignant Brain Tumor (MBT) domains that recognize methylated lysines on histone tails. Like dL(3)MBT, hL(3)MBTL1 acts as a chromatin compaction factor that represses transcription and inhibits cytokinesis in GBM cell lines. The highly hypoxic tumor microenvironment (TME) in GBM drives its progression, recurrence, and therapeutic resistance. However, it remains unclear if L(3)MBTL1 is regulated by TME cues to promote GBM growth. Based on this knowledge gap and our preliminary data, we hypothesize that hypoxia directly regulates L(3)MBTL1 in favor of GBM growth. Analysis of TCGA data for IDH-wildtype gliomas revealed that L3MBTL1 gene expression is downregulated in GBM, which are necrotic and severely hypoxic, compared to histologic grade 2/3 gliomas, which do not contain necrosis, indicating that hypoxia could potentially suppress L3MBTL1 to enhance glioma progression. TCGA data also revealed a number of HIF pathway and hypoxia-inducible genes strongly correlating with L3MBTL1 expression, including HIF1a and VHL. Using patient-derived GBM neurosphere cultures, we exposed glioma cells to hypoxia (1% O2 for 24hrs) and found that L3MBTL1 protein levels were suppressed compared to normoxia (21%). Under these same conditions, we found more rapid cell proliferation under hypoxia. Exploration of hypoxic TME regulation of the novel tumor suppressor L3MBTL1 in glioma progression has the potential to uncover novel mechanisms involving epigenetic modulation and potentially new therapeutic strategies.